2020
DOI: 10.1038/s41598-020-69495-w
|View full text |Cite
|
Sign up to set email alerts
|

Human pluripotent stem cell-derived cardiomyocytes as a target platform for paracrine protection by cardiac mesenchymal stromal cells

Abstract: ischemic heart disease remains the foremost cause of death globally, with survivors at risk for subsequent heart failure. Paradoxically, cell therapies to offset cardiomyocyte loss after ischemic injury improve long-term cardiac function despite a lack of durable engraftment. An evolving consensus, inferred preponderantly from non-human models, is that transplanted cells benefit the heart via early paracrine signals. Here, we tested the impact of paracrine signals on human cardiomyocytes, using human pluripote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…MicroRNAs are emerging players in cardiomyocyte proliferation and have been shown to modulate it by predominantly targeting components of the Hippo pathway [ 108 ]. For example, microRNA-199a, which promotes cardiomyocyte proliferation by targeting the Hippo pathway regulators TAOK1 and β-TrCP, was found to be expressed in CDC-derived extracellular vesicles [ 60 , 108 , 109 ]. Delivery of the secretome of MSCs or CPCs has been shown to be sufficient to induce cardiac repair following MI [ 60 , 110 , 111 ].…”
Section: Cell Therapy — Mechanisms Of Action and Current Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…MicroRNAs are emerging players in cardiomyocyte proliferation and have been shown to modulate it by predominantly targeting components of the Hippo pathway [ 108 ]. For example, microRNA-199a, which promotes cardiomyocyte proliferation by targeting the Hippo pathway regulators TAOK1 and β-TrCP, was found to be expressed in CDC-derived extracellular vesicles [ 60 , 108 , 109 ]. Delivery of the secretome of MSCs or CPCs has been shown to be sufficient to induce cardiac repair following MI [ 60 , 110 , 111 ].…”
Section: Cell Therapy — Mechanisms Of Action and Current Limitationsmentioning
confidence: 99%
“…For example, microRNA-199a, which promotes cardiomyocyte proliferation by targeting the Hippo pathway regulators TAOK1 and β-TrCP, was found to be expressed in CDC-derived extracellular vesicles [ 60 , 108 , 109 ]. Delivery of the secretome of MSCs or CPCs has been shown to be sufficient to induce cardiac repair following MI [ 60 , 110 , 111 ]. For example, administration of exosomes isolated from human CDCs significantly repressed scarring and improved cardiac function in a porcine MI model [ 111 ].…”
Section: Cell Therapy — Mechanisms Of Action and Current Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely restoration of blood perfusion by drug thrombolysis or interventional surgery is the key to the clinical rescue of patients with MI (Pluijmert et al, 2021; Wang et al, 2017). Large parts of studies have revealed that after blood reperfusion, reactive oxygen species (ROS) will be largely released and induce myocardial cell apoptosis and autophagy, thus seriously affecting the prognosis of patients with MI (Arab et al, 2007; Constantinou et al, 2020; Dlamini et al, 2015; Schiattarella & Hill, 2016; Zhang et al, 2017). Either autophagy or apoptosis is a highly regulated biological event that deeply influences tissue homeostasis, development, and disease (Eisenberg-Lerner et al, 2009; Fuchs & Steller, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…PDGFRA is a transmembrane tyrosine kinase receptor activated by PDGFA and PDGFC ( 17 , 18 ). During cardiac development, PDGFRA is implicated in a spectrum of physiologic and pathologic processes, including cell growth and survival ( 19 , 20 ), stem cell differentiation ( 16 , 21 ), and migration ( 13 , 22 ). Following development, both alpha and beta cardiac PDGFRs become silent.…”
Section: Introductionmentioning
confidence: 99%